Real-World Snapshot of Dietary Patterns in Subjects Living with Chronic Kidney Disease. - Di Lorenzo, Mariana; Lonardo, Maria Serena; Di Lauro, Mariastella; Chiurazzi, Martina; de Giovanni di Santa Severina, Anna Fiorenza; Capuano, Marcella; Guida, Bruna; Trio, Rossella; Pacella, Daniela; Memoli, Andrea; Esposito, Simona (Nutrients, 2025)
Background/Objectives: Chronic kidney disease (CKD) represents a major global public health challenge. Diet plays a central role in CKD management, with guidelines emphasizing individualized intake of energy, macronutrients, and micronutrients in combination with medical treatment. In recent years, increasing attention has been directed toward diet quality and the degree of food processing, particularly the consumption of ultra-processed foods (UPFs), which have been linked to adverse metabolic and renal outcomes. However, limited data are available on the real-life dietary patterns of individuals with CKD who have not yet received structured nutritional counseling. This study aims to describe the dietary habits of adults with CKD compared to healthy controls, in order to better understand nutritional challenges and identify potential targets for dietary intervention in CKD management. Methods: 73 subjects (46.6% M) were enrolled; they attended the Outpatients Clinic of the I.P. "Diet Therapy in transplantation, renal failure and chronic pathology", University of Naples Federico II. Subjects were divided into two groups based on the presence/absence of CKD, established on the basis of a glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2. Each participant was evaluated for biochemical parameters, anthropometric measurements, body composition, and dietary assessment. Results: CKD group showed a lower caloric intake compared to Control Group. In particular, lipid intake was significantly higher in Control Group whereas carbohydrates intake was higher in CKD Group. No difference was found between the two groups regarding daily protein intake. Dietary sodium and salt intake was found to be lower in CKD Group compared to Control Group and the latter showed a lower omega-6/omega-3 ratio. Interestingly, the consumption of UPF was higher in Control Group compared to CKD Group. Conclusions: This study offers a snapshot of the dietary habits of a cohort from Southern Italy CKD stage 3–5 patients, showing that even in the absence of specific nutritional guidance, individuals were able to implement small lifestyle changes such as UPF and salt intake reduction. However, critical nutritional imbalances in CKD patients show the limits of self-managed diets, highlighting the need for structured nutritional support.